Highly efficient cosensitization of D–A–π–A benzotriazole organic dyes with porphyrin for panchromatic dye-sensitized solar cells. Issue 42 (6th October 2015) - Liu, Jingchuan; Liu, Bo; Tang, Yunyu; Zhang, Weiwei; Wu, Wenjun; Xie, Yongshu; Zhu, Wei-Hong
Abstract : The optimization between the pure organic dye and the porphyrin sensitizer, and their effects on photovoltaic performance are focused, achieving a strong panchromatic light response and a promising photovoltaic efficiency of 10.41% with only 6 μm TiO2 films. Abstract : Compared with the development of novel organic sensitizers, cosensitization is a much more convenient way to acquire panchromatic dye-sensitized solar cells (DSSCs). Taking the strong absorption in the long wavelength region but the lack of response in the ranges of 350–410 nm and 500–600 nm of porphyrin dyes into account, the D–A–π–A benzotriazole organic dye (WS-5 ), showing strong absorption bands in these two ranges, is targeted for cosensitization with porphyrin dyeXW4 . The cosensitization effects on light-harvesting capability, photovoltaic performance, charge recombination as well as long-term stability have been investigated in detail, especially for the interactions betweenWS-5 andXW4 and their effects on photovoltaic performance. Noticeably, a strong panchromatic light response and a promising photovoltaic efficiency of 10.41% have been achieved with only 6 μm TiO2 films, which is obviously higher than the corresponding efficiencies obtained using a single sensitizer. The cosensitization is essentially dominated byWS-5 while only a small amount ofXW4 is contributed to enhance the IPCE response in the long wavelength region. These results demonstrate the effective approach for utilizing porphyrin dyes to simultaneously fill up the absorption valleys of D–A–π–A featured sensitizers and promote the DSSC efficiency, presenting the effective strategy of cosensitization to combine the advantages of both porphyrin and organic dyes, especially for pursuing highly efficient panchromatic dye-sensitized solar cells.